The Sistem Pengendalian Manajemen dan Implementasi Aplikasi Internet Mobile Banking untuk Meningkatkan Kinerja Karyawan pada PT. Bank Syariah Indonesia - Bukran, Bukran; Jati, Lalu Jatmiko (Income : Digital Business Journal, 2024)
Management control system is a system used by management to influence members of the organization to carry out organizational strategies and policies efficiently and effectively in order to achieve organizational goals. Employee performance is one of the factors in measuring the success of the company's control system, an individual's ability to do the job in accordance with what has been given to him. This study aims to determine the effect of management control system efficiency on employee performance at Bank Syariah Indonesia KC Mataram. Bank Syariah Indonesia is a company that recently merged with 3 other Islamic bank companies. This type of research uses qualitative research methods. Qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects. With this merger, researchers want to know whether there is a decrease or increase in the quality of employee performance.